Characteristics of international business development between ukraine and poland (Economics and region, 2019)
The essence of international business, its active development and expansion, that influence the integration of economic systems and intensification of business relations between countries, are considered. The attention is paid to the international market of the European Union, first of all to Polish-Ukrainian cooperation due to the modern development of international business. The importance of the development of trade and business between Ukraine and Poland is determined, taking into account close relations in the field of economy, politics, culture and historical connections. The legal framework between Ukraine and Poland is substantiated, which ensures the proper development of bilateral cooperation at the level of strategic partnership and emphasizes the presence of an active dialogue between countries. The main agreements between Ukraine and the European Union, which influence the economic cooperation between Ukraine and Poland, are considered, taking into account Polish membership in the EU. The implementation of special projects by the European Union to support the development of Polish-Ukrainian cooperation is determined. The increase of the intensity of economic exchange between Ukraine and Poland, the active development of trade and investment in various spheres of business and the growth of economic indicators are determined. The peculiarities of the development of the small business sector and its influence on the stabilization of socio-economic processes between European countries are substantiated, emphasizing Poland's experience in development of the small business as a driving force on the way to economic integration. The main aspects and characteristics of international business between Poland and Ukraine are determined and the main differences in doing business in these countries are revealed, emphasizing the perspectives of development.
Keywords: international business; characteristics; development; cooperation; EU; integration